Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b) x^2 y^2 + xy + x^3 + y^3
Tai x = -1 ,y = -3 ta co
(-1)^2 (-3)^2 + (-1 ) (-3) + (-1)^3 + (-3)^3
=> 1 x 9 -4 + ( -1) + (-27 )
=> 5 - 28
=> -23
1 + 22 + 23 + ... + 22005
Gọi dãy số trên là A
A = \(1+2^2+2^3+....+2^{2005}\)
A =\(2^0+2^2+2^3+....+2^{2005}\)
A + \(2^1\)= \(2^0+2^1+2^2+2^3+....+2^{2005}\)
( A + 2 ) x 21 = \(\left(2^0+2^1+2^2+2^3+....+2^{2005}\right)\times2^1\)
Ax2 + 4 =\(2^1+2^2+2^3+2^4+....+2^{2006}\)
4 + A x 2 - A =\(2^1+2^2+2^3+2^4+....+2^{2006}-\left(1+2^2+2^3+...2^{2005}\right)\)
4 + A = \(2^1+2^2+2^3+2^4+....+2^{2006}-1-2^2-2^3-....-2^{2005}\)
4 + A = \(2^{2006}-1\)
A=\(2^{2006}-1-4\)
A = \(2^{2006}-5\)
Mà \(2^{2006}-5< 2^{2006}\)
\(\Rightarrow1+2^2+2^3+....+2^{2005}< 2^{2006}\)
Có : 7A = 7+7^2+....+7^2015
6A=7A-A=(7+7^2+....+7^2015)-(1+7+7^2+....+7^2014) = 7^2015-1
=> A = (7^2015-1)/6
k mk nha
Ta có
\(M=1+\left(-2\right)+\left(-2\right)^2+...+\left(-2\right)^{2006}\)
\(M=\left(-2\right)^0+\left(-2\right)^1+\left(-2\right)^2+...+\left(-2\right)^{2006}\)
\(-2M=\left(-2\right)^1+\left(-2\right)^2+\left(-2\right)^3+...+\left(-2\right)^{2007}\)
\(3M=M-\left(-2M\right)=\left(-2\right)^0-\left(-2\right)^{2007}\)
\(\Rightarrow M=\frac{3M}{3}=\frac{1+2^{2007}}{3}\)